Homecoming : a novel - Morton, Kate, 1976- (New York : Mariner Books, 2023)
Called home to care for her grandmother after a fall, Jess, a journalist, discovers a book chronicling the police investigation into an old unsolved murder that has a shocking connection to her family
"The highly anticipated new novel from the New York Times bestselling author of The Clockmaker's Daughter, a sweeping novel that begins with a shocking crime, the effects of which echo across continents and generations. Adelaide Hills, Christmas Eve, 1959: At the end of a scorching hot day, beside a creek on the grounds of a grand country house, a local man makes a terrible discovery. Police are called, and the small town of Tambilla becomes embroiled in one of the most baffling murder investigations in the history of South Australia. Many years later and thousands of miles away, Jess is a journalist in search of a story. Having lived and worked in London for two decades, she now finds herself unemployed and struggling to make ends meet. A phone call out of nowhere summons her back to Sydney, where her beloved grandmother Nora, who raised Jess when her mother could not, has suffered a fall and is seriously ill in the hospital. At Nora's house, Jess discovers a true crime book chronicling a long-buried police case: the Turner Family Tragedy of 1959. It is only when Jess skims through its pages that she finds a shocking connection between her own family and this notorious event--a mystery that has never been satisfactorily resolved. An epic story that spans generations, Homecoming asks what we would do for those we love, how we protect the lies we tell, and what it means to come home. Above all, it is an intricate and spellbinding novel from one of the finest writers working today"--
Originally published in Australia in 2023 by Allen & Unwin
Keywords: Women journalists -- Fiction; Grandmothers -- Fiction; Murder -- Fiction; Family secrets -- Fiction; Cold cases (Criminal investigation) -- Fiction; Homecoming -- Fiction; FICTION / World Literature / Australia; FICTION / Women; FICTION / Historical; FICTION / Literary; FICTION / Mystery & Detective / Historical; FICTION / Mystery & Detective / Women Sleuths; FICTION / Sagas; Grandmothers; Murder; Women journalists; Sydney (N.S.W.) -- Fiction; New South Wales -- Sydney; Detective and mystery fiction; Fiction; Novels; Thrillers (Fiction); Detective and mystery fiction; Thrillers (Fiction); Domestic fiction; Novels